2014
DOI: 10.1007/s12663-014-0726-5
|View full text |Cite
|
Sign up to set email alerts
|

Management and Treatment Outcomes of Maxillofacial Fibro-osseous Lesions: A Retrospective Study

Abstract: Introduction Fibro-osseous lesions are a diverse group of bone disorders and include developmental, reactive or dysplastic diseases and neoplasms. They share overlapping clinical, radiographic and histopathologic features and demonstrate a wide range of biological behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…3,12,24,25 Despite the apparent bone fragility that supposedly results from fibrous dysplasia, which could contraindicate or make surgery more difficult, whether lesion resection or plasty, a low rate of surgical complications can be observed. 2,3 There is no consensus in the literature as for lesion growth recurrence, where some studies have shown recurrence in up to 50% of the cases, with a mean time of 6.6 years. Other studies do not show recurrence in a mean 9-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,12,24,25 Despite the apparent bone fragility that supposedly results from fibrous dysplasia, which could contraindicate or make surgery more difficult, whether lesion resection or plasty, a low rate of surgical complications can be observed. 2,3 There is no consensus in the literature as for lesion growth recurrence, where some studies have shown recurrence in up to 50% of the cases, with a mean time of 6.6 years. Other studies do not show recurrence in a mean 9-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroosseous lesions comprise a group of benign pathological entities associated with disordered collagen deposition and immature matrix ossification 12. These lesions can be classified into three types: fibrous dysplasia, bone dysplasia, and ossifying fibroma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Radical surgery including local resection, marginal resection and total resection with or without reconstructive surgery. Most of studies implemented 2 type of surgery (radical and conservative surgery) in their patient, only 1 study (Kumar et al [9]) reported using radical surgery to treat all their patients. Radical surgery was the most preferable treatment that chosen by surgeon based on this review with percentage 35.7% compared with conservative surgery with percentage 28.6%.…”
Section: Type Of Surgerymentioning
confidence: 99%
“…Waldron stated the lesion usually describe as pathological changes within the jaw bones, in which normal bone is replaced by fibrous tissue with or without calcification. They frequently develop in the craniofacial region, especially in the jaws, the nasal cavity, the paranasal sinuses and the orbit [2]. They are divided into 3 different entities, namely osteoma, fibrous dysplasia (FD) and ossifying fibroma (OF).…”
Section: Introductionmentioning
confidence: 99%